Redefining Strategies to Introduce Tolerance-Inducing Cellular Therapy in Human beings to Combat Autoimmunity and Transplantation Reactions - ten Brinke, Anja; Joosten, Irma; van Ham, S. Marieke; van Kooten, Cees; Prakken, Berent Jan (Frontiers in Immunology, 2014)
Clinical translation of tolerance-inducing cell therapies requires a novel approach focused on innovative networks, patient involvement and, foremost, a fundamental paradigm shift in thinking from both Academia, Industry and Regulatory Agencies. Tolerance-inducing cell products differ essentially from conventional drugs. They are personalized and target interactive immunological networks to shift the balance towards tolerance. The human cell products are often absent or fundamentally different in animals. This creates important limitations of pre-clinical animal testing for safety and efficacy of these products and calls for novel translational approaches, which require the combined efforts of the different parties involved. Dedicated international and multidisciplinary consortia that focus on clinical translation are of utmost importance. They can help inform and educate regulatory policy makers on the unique requirements for these cell products, ranging from preclinical studies in animals to in vitro human studies. In addition, they can promote reliable immunomonitoring tools. The development of tolerance-inducing cell products requires not only bench-to-bedside but also reverse translation, from bedside back to the bench.